Behavioural Response of Whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) Towards Volatile Organic Compounds Emitted from Eggplant Leaves - Amina Raed; Qasim Ahmed; Mokhtar Abdulsattar Arif (Al-Mustansiriyah Journal of Science, 2023)
The whitefly Bemisia tabaci is considered one of the most destructive insect pests that can attack several vegetable crops worldwide. The behavior of choosing a host plant by whitefly can be significantly influenced by volatile organic compounds. The aim of this investigation is to identify and bioassay the volatile organic compounds emitted from uninfested and infested eggplant leaves with B. tabaci. The current study focuses on the interaction between whitefly and eggplant with the identification of volatile organic compounds emitted from leaves that were collected by headspace solid phase microextraction fiber and gas chromatography mass spectrum analyzed. Both uninfested and infested eggplant leaves released a total of 11 compounds. The amount of volatile organic compounds emitted from affected eggplant leaves by whitefly was higher than from uninfested eggplant leaves. Using a Y-shaped olfactometer bioassay, whitefly preferred to attract toward volatile emitted by eggplant leaves in both uninfested and infested eggplant leaves. Our results suggest these chemical compounds can play a key mediator in host finding behavior. The exploitation of one or more of these compounds can apply in an integrated management program of this pest as a lure in the sticky trap or manipulating insect behavior.